"Blue" Morality and the Legitimacy of the State—Ed Rubin's Soul, Self, and Society: The New Morality and the Modern State. Issue 2 (25th August 2016) - Carbone, June
Abstract : Ed Rubin's provocative new book, Soul, Self, and Society: The New Morality & the Modern State (2015), attempts to capture the relationship between morality and the state. It maintains that that there are three comprehensive moral systems: the morality of honor that characterized feudal relationships and survives today in failed states and urban gangs, the morality of higher purposes that linked individual self‐worth and state legitimacy to a shared belief system, and the morality of self‐fulfillment that entrusts development of a moral code to each individual and sees the role of the state as creating the conditions for individual flourishing. This review essay argues that Rubin's work is critically important in explaining that the idea of self‐fulfillment combines public tolerance with private discipline, and rests on obligation as well as freedom. It suggests, however, that if the new morality were to truly take hold, it would weaken the links between citizen and state that make the system possible.